Experimental treatment of a refinery waste air stream, for BTEX removal, by water scrubbing and biotrickling on a bed of Mitilus edulis shells - Torretta, Vincenzo (Environmental technology, 2015)
The paper presents the results of a two-stage pilot plant for the removal of benzene, toluene, ethylbenzene and xylene (BTEX) from a waste air stream of a refinery wastewater treatment plant (WWTP). The pilot plant consisted of a water scrubber followed by a biotrickling filter (BTF). The exhausted air was drawn from the main works of the WWTP in order to prevent the free migration to the atmosphere of these volatile hazardous contaminants. Concentrations were detected at average values of 12.4 mg Nm(-3) for benzene, 11.1 mg Nm(-3) for toluene, 2.7 mg Nm(-3) for ethylbenzene and 9.5 mg Nm(-3) for xylene, with considerable fluctuation mainly for benzene and toluene (peak concentrations of 56.8 and 55.0 mg Nm(-3), respectively). The two treatment stages proved to play an effective complementary task: the water scrubber demonstrated the ability to remove the concentration peaks, whereas the BTF was effective as a polishing stage. The overall average removal efficiency achieved was 94.8% while the scrubber and BTF elimination capacity were 37.8 and 15.6 g BTEX d(-1) m(-3), respectively. This result has led to outlet average concentrations of 1.02, 0.25, 0.32 and 0.26 mg Nm(-3) for benzene, toluene, ethylbenzene and xylene, respectively. The paper also compares these final concentrations with toxic and odour threshold concentrations